2014
DOI: 10.1037/scp0000003
|View full text |Cite
|
Sign up to set email alerts
|

Anger concepts and anger reduction method in Theravada Buddhism.

Abstract: This article examines anger concepts and an anger reduction method found in Theravada Buddhist Sutta-pitaka scripture. The scripture defines anger, discusses its origin, anger-related behaviors and consequences, and suggests an anger reduction method that involves not responding to anger provocation, treating others with loving kindness, and neither seeking revenge nor using violent means. Buddhist anger concepts and the anger reduction method are supported by extensive social psychological research. Buddhist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(91 reference statements)
0
1
0
1
Order By: Relevance
“…While the following study findings are not generalizable to all clients of a particular religious or spiritual orientation they may help to underscore how appropriate assessment can reveal intersectional components for a given presenting problem. Ariyabuddhiphongs (2014) found that Buddhist clients may view anger as a provoked response that is under the control of the individual. When these responses lead to negative thoughts, emotions, and behaviors a Buddhist client may perceive this as a spiritual imbalance that can foster hatred and other unwanted repercussions.…”
Section: Psychological Research On Spirituality and Angermentioning
confidence: 99%
“…While the following study findings are not generalizable to all clients of a particular religious or spiritual orientation they may help to underscore how appropriate assessment can reveal intersectional components for a given presenting problem. Ariyabuddhiphongs (2014) found that Buddhist clients may view anger as a provoked response that is under the control of the individual. When these responses lead to negative thoughts, emotions, and behaviors a Buddhist client may perceive this as a spiritual imbalance that can foster hatred and other unwanted repercussions.…”
Section: Psychological Research On Spirituality and Angermentioning
confidence: 99%
“…Não é raro que o sentimento fuja do controle e resulte em hostilidade, agressões e/ou comportamentos de risco (direção ofensiva, por exemplo). Reagindo à raiva e estando o indivíduo muitas vezes incapaz de refletir antes da ação, a expressão da emoção pode ocasionar consequências importantes (e às vezes irreversíveis) na vida de uma pessoa e daqueles ao seu redor (Ariyabuddhiphongs, 2014;Short, 2016). Ressalta-se, todavia, que a subutilização da raiva pode ser igualmente prejudicial (Lombardi-Rech & Giacomoni, 2020).…”
unclassified